The Effect of Operational Costs and Revenue on the Financial Performance of Type C Regional Hospitals in Bangka Belitung - David Herryanto; Abdul Gani Sidqi; Ayu Laili Rahmiyati (Journal of Economics and Management Scienties, 2026)
For type C hospitals that provide non-JKN services, measurable and transparent financial performance is an important foundation for ensuring effective management and operational sustainability. Financial reports not only reflect the economic condition of the organization, but also serve as an evaluation tool to assess service efficiency and growth opportunities. As health care institutions, hospitals are required to continuously improve service quality while optimizing their performance to meet the ever-evolving expectations of the community. This study aims to analyze the effect of operational cost budgets and revenue budgets on the financial performance of type C hospitals in the Bangka Belitung Islands Province, both partially and simultaneously. The approach used is quantitative descriptive with a population of all type C hospitals in the province, both government and private. The sample was selected using purposive sampling, resulting in 33 observation units from 11 hospitals in the 2021–2023 period. The data were analyzed using a panel data regression model. The results show that the operating budget has a positive and significant effect on financial performance partially, while the revenue budget does not show a significant effect partially. Simultaneously, the operating budget and revenue budget together affect hospital financial performance. The conclusion of this study confirms that effective operating budget management is a key factor in driving optimal financial performance, so hospitals need to prioritize operational spending efficiency as a strategy for continuous performance improvement.